ENHANCING VOCABULARY MASTERY OF KINDERGARTEN STUDENTS THROUGH DIFFERENTIATED INSTRUCTION - Ridha Ilma Ilma; Rahma Dianti (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2016)
Abstract: This study was aimed at examining the application of differentiated instruction in enhancing vocabulary mastery to the students of TK ARKAAN Palembang. This study was a classroom action research. Test and observation were the instruments to collect the data. This study consisted of two cycles, cycle I and cycle II. Planning, implementation, observation, and reflection were the phases of the study. Thirty three of students of TK ARKAAN Palembang were the sample of the study. Data calculation showed that there was a significant improvement of students’ vocabulary mastery, the means score in cycle I was 48.48 and in cycle II was 86.36. In other words, the improvement of students’ vocabulary score was 37.88. Then, there was also significant improvement of students learning completeness. The learning completeness in cycle I was 24.25% and cycle II was 90.90% and the improvement was 66.65%. In other words, vocabulary mastery of students at TK ARKAAN Palembang was enhanced by using differentiated instruction. The students’ perception toward the implementation of differentiated instruction was good. Keywords: vocabulary mastery, differentiated instruction, kindergarten students